OPTIMALISASI POLA USAHATANI LAHAN RAWA LEBAK DI KAWASAN PEMULUTAN KABUPATEN OGAN ILIR SUMATERA SELATAN (JASEP, 2015)
Optimum land for food plants becoming decrease. Sub optimal land become alternative way for government to gain food self-sufficient specifically for paddy. Pemulutan area in Ogan Ilir Regency is one of sub optimal land for agriculture which typology is swamp land. Farmers in this area rearrengements their commodity without calculating in economics. This caused the income that they accepted can not be maximum because of agriculture pattern. The aimed of this research were 1) to determine what is the agriculture pattern that can earn maximum income, 2) to find out whats the problem thas why paddy’s farmer in swamp land area can not be applied the optimal pattern. The method used in this research was Linear Programing Model with ABQM program. The results showed that the agriculture pattern that recommended in shallow swamp land is chili and bean, in middle swamp land is corn, chili and bean and in the deep swamp land we can only plant paddy. The pattern of agriculture that mentioned can increase the income of the farmers is about Rp. 13.164.269,60. The fence that farmers can not apply this pattern is the land that is limited, and the flooded area or water fluctuation so that farmers only plant once a year which caused many worker can not allocation use theit time effectively.